Use of regional limb perfusion with amikacin sulphate in the treatment of a severe soft tissue infection in the extremity of a dog. Issue 1 (6th February 2019) - Abrams, Brittany E; Hottinger, Heidi; Selmic, Laura Elizabeth
Abstract : Intravenous regional limb perfusion (RLP) has been used extensively in equine and human practice to deliver high doses of antimicrobials to bones, joints and the soft tissues in the distal limb. This report highlights the use of this technique, in conjunction with traditional systemic antimicrobial therapy, to achieve clinical resolution of a severe soft tissue infection in the extremity of a dog. Due to the acute severity, rapid progression and lack of response of the infection to broad‐spectrum systemic antibiotics, intravenous RLP with amikacin was utilised successfully, negating the need to intervene with definitive surgery. To the authors' knowledge, this is the first report utilising intravenous RLP as an adjuvant antimicrobial treatment application in a small animal setting.